The effect of psychological contract on job related outcomes: The moderating effect of stigma consciousness - Annis Pramudita; Badri Munir Sukoco; Wann-Yih Wu; Indrianawati Usman (Cogent Business & Management, 2021)
This study examines how employees' tendencies with regard to relational or transactional contract could influence job related outcomes. The typology then relates to the stigma consciousness that each employee has regarding their employment status, as either temporary or permanent workers. This study argues that each worker has their own expectations with regard to being stigmatized due to their status employment, and this could then strengthen/weaken the relationships between relational or transactional contract on job related outcomes. The proposed hypotheses are validated through two cross-sectional studies in two different organizations in Indonesia. The findings indicate that there are positive relationships between individuals who predominantly hold relational contract and their job satisfaction and job performance, and less intention to quit. However, the opposite effects for transactional contract are not revealed in this study, which might be due to the cultural values of the sample. Further, the positive relationships of relational contract on job satisfaction and contextual performance are weakened when the respondents have high stigma consciousness, while the relationship with intention to quit is strengthened. Additional findings indicate that individuals who predominantly hold transactional contract tend to have less job satisfaction when they are highly stigma conscious. The academic and managerial implications of this work are also discussed in this study.
Keywords: 650; relational contract; transactional contract; stigma consciousness; job related outcomes